Speech Prosody 2018 2018
DOI: 10.21437/speechprosody.2018-31
|View full text |Cite
|
Sign up to set email alerts
|

Vowel space and f0 characteristics of infant-directed singing and speech

Abstract: When adults talk to infants, they dramatically change the prosodic and acoustic structure of speech. Recently, new insights have been gained on those changes, especially on the vocalic and temporal structure of speech which are described as being more variable than in adult conversations. In the present contribution, we examine formant and fundamental frequency characteristics of different infant-directed registers, notably infant-directed speech and singing, the latter not being investigated so far. We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Thus, the observed positivity in the song familiarization could reflect additional challenges segmenting words from songs, such as the atypical acoustic signal of sung compared to spoken language [41,42]; cf. [43], or the increased risk of mis-segmentations from songs [44,45,123]. Alternatively, the acoustic focus and speaking rate might not explain the positive-going response in the present speech familiarization either, in which case we need to look to other factors to explain the different result patterns across studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, the observed positivity in the song familiarization could reflect additional challenges segmenting words from songs, such as the atypical acoustic signal of sung compared to spoken language [41,42]; cf. [43], or the increased risk of mis-segmentations from songs [44,45,123]. Alternatively, the acoustic focus and speaking rate might not explain the positive-going response in the present speech familiarization either, in which case we need to look to other factors to explain the different result patterns across studies.…”
Section: Discussionmentioning
confidence: 87%
“…Firstly, infants' speech-honed language-learning skills may not be successful when applied to the acoustic signal of songs: lyrics sung to a melody are produced with different acoustic features than regular speech [41], including a more compressed and less consistently produced acoustic vowel space [42], cf. [43]. Secondly, even adults at times mishear words in songs, both in their non-native and native language [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…While higher and more variable pitch might be the two robust characteristics of IDS present across cultures and languages (Broesch & Bryant, 2015;Farran et al, 2016;McClay et al, 2021;Narayan & McDermott, 2016; but see also Han et al, 2020Han et al, , 2021, vowel space expansion, on the other hand, has not been reported consistently across languages. For instance, increased vowel space expansion in IDS vs. ADS has not been found in Dutch (Benders, 2013), German (Audibert & Falk, 2018), Cantonese (Xu Rattanasone et al, 2013), Lenakel and Southwest Tanna (McClay et al, 2021), and inconsistently reported in Norwegian (Englund & Behne, 2006;Kartushina, Robbestad, et al, 2021). Further, experimental studies have found that neither British (Floccia et al, 2016) or German (Schreiner & Mani, 2017) infants segment speech stimuli recorded in natural IDS register in their respective languages, unless these are prosodically exaggerated over and beyond what would be considered 'natural' British and German IDS.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is surprising given that vowel hyperarticulation in mothers’ IDS has been proposed to facilitate speech processing and subsequent language acquisition (Kuhl, ). However, this “facilitation” view is not uncontroversial (Cristia, ), as a number of studies have failed to detect vowel hyperarticulation in maternal speech in English (e.g., Green, Nip, Wilson, Mefferd, & Yunusova, ) and other languages (e.g., German—Audibert & Falk, ; Dutch—Benders, ; and Norwegian—Englund & Behne, ). Furthermore, even in cases in which vowel hyperarticulation is present, it has been found to co‐occur with a high degree of within‐category variability, which may exacerbate the difficulty of infants’ task of learning discrete phonological categories in their native language (Cristia & Seidl, ; McMurray, Kovack‐Lesh, Goodwin, & McEron, ).…”
Section: Introductionmentioning
confidence: 99%